An Analysis on the Impact of TOEFL Course Program on English Proficiency Level of Final Year Polytechnic Students in Politeknik Pertanian Negeri Payakumbuh - Widya Febrina; Meriyan Elza; Resa Yulita; Hudia Hudia; Yuliandri Yuliandri (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to evaluate the impact of the TOEFL program implemented for Polytechnic students in improving their English proficiency. This research was conducted in Politeknik Pertanian Negeri Payakumbuh. The background of this research is based on the significance of English mastery as one of the graduation prerequisites and as preparation for entering the workforce. The research method employed is a quantitative approach using a pretest and post-test design. The research sample was formed from 26 students who participated in the TOEFL program for one semester. The participants were eighth-semester students of the Computer Engineering Technology Study Program at Politeknik Pertanian Negeri Payakumbuh. Data were collected through institutional TOEFL tests administered before and after the program implementation. The data indicate that the TOEFL training program significantly improved students’ English proficiency and listening skill was the skill that experienced the highest improvement.